2022
DOI: 10.1101/2022.11.03.22281890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omics endotype of preterm infants with bronchopulmonary dysplasia and pulmonary hypertension

Abstract: Rationale: Pulmonary hypertension associated with bronchopulmonary dysplasia is a severe complication of preterm birth resulting in high mortality of up to 50% within the first 2 years of life. There is a direct relationship between bronchopulmonary dysplasia severity and incidence of associated pulmonary hypertension. However, it is challenging to clinically characterize severe bronchopulmonary dysplasia with and without pulmonary hypertension and there is need for better understanding of the two entities. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…As a glycosylated protein, it acts as a ligand for several galectins, such as galectin-3 [66]. Siddaiah et al (2022) reported a significant increase in LGALS3BP levels in tracheal aspirates from infants with severe bronchopulmonary dysplasia with PH [67].…”
Section: Plos Onementioning
confidence: 99%
“…As a glycosylated protein, it acts as a ligand for several galectins, such as galectin-3 [66]. Siddaiah et al (2022) reported a significant increase in LGALS3BP levels in tracheal aspirates from infants with severe bronchopulmonary dysplasia with PH [67].…”
Section: Plos Onementioning
confidence: 99%